2012
DOI: 10.1007/s11262-012-0849-z
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of avian influenza virus NS1 protein and nucleolar and coiled-body phosphoprotein 1

Abstract: Nonstructural protein 1 (NS1) is a non-structural protein of avian influenza virus. It can interact with a variety of proteins of the host cells, enhancing the expression of viral proteins and changing the growth and metabolism of the host cells, thereby enhancing the virus’ pathogenicity and virulence. To investigate whether there are more host proteins that can interact with NS1 during viral infection, T7-phage display system was used to screen human lung cell cDNA library for proteins that could interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The NES is located between amino acids 138-147 (Li, Yamakita et al 1998). A virus strain specific nucleolar localization (NoLS) signal has also been identified which overlaps with NLS2 (Melen, Kinnunen et al 2007;Melen, Tynell et al 2012;Zhu, Zheng et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The NES is located between amino acids 138-147 (Li, Yamakita et al 1998). A virus strain specific nucleolar localization (NoLS) signal has also been identified which overlaps with NLS2 (Melen, Kinnunen et al 2007;Melen, Tynell et al 2012;Zhu, Zheng et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the NS1 protein of IAV can interact with NOLC1 [9,15]. The present study explored this phenomenon further by identifying which portion of the NS1 protein is necessary for its interaction with NOLC1 and which amino acid residues are involved in the interaction.…”
Section: Discussionmentioning
confidence: 84%
“…NS1 consists of two domains, an N-terminal RNA-binding domain and a C-terminal effector domain. It is the effector domain that is responsible for the many interactions between NS1 and other proteins such as P85b, PARP10, CPSF30, and NOLC1 [1][2][3]9], and therefore, we speculated that the region of the protein that would participate in the binding with NOLC1 might also lie in the effector domain. NS1 can also prevent the host cell from undergoing apoptosis to ensure that the virus can replicate efficiently in the cell [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NS1 has gained motifs in its CTT which have conferred to NS1 the ability to interact with a wider collection of proteins [107]. There is evidence in the literature that NS1 may interact with the following additional partners: human PAF1 transcription elongation complex (hPAF1C); parafibromin (CDC73), global transcription activator (SNF2L) [108]; chromodomain-helicase-DNA-binding protein 1 (CHD1) [109]; WD repeat-containing protein-5 (WDR5) [109]; β-tubulin [110]; nucleolin, fibrillarin, and nuclear B23 [70]; RNA-associated protein 55 (RAP55) [111]; RNA binding protein nuclear factor 90 (NF90) [112]; heat shock protein 90 (HSP90) [113]; NOD-like receptor family, pyrin domain containing 3 protein (NLRP3) [114]; inhibitor of nuclear factor kappa-B kinase subunits α and β (IKKα and IKKβ) [115]; poly(a)-binding protein II (PABII) [89]; human guanylate-binding protein 1 (hGBP1) [116]; transcription factors p53 and cleavage and polyadenylation specificity factor subunit 4 (CPSF4) [117]; PDZ and LIM domain protein 2 (PDlim2) [118]; membrane-associated guanylate kinase inverted 1, 2 and 3 (MAGI-1,2 and 3, respectively), scribble and discs large homolog 1 (Dlg-1) [119,120]; tyrosine-protein kinase Src (c-Src), tyrosine-protein phosphatase non-receptor type 1 (PTPL1) and reversion-induced LIM protein (RIL) [121]; and adapter molecule crk (CrkI and CrkII) [107].…”
Section: Function and Protein-protein Interactionsmentioning
confidence: 99%